Lifestyle assessment in two age groups of ischemic stroke: A cross-sectional study in Iran - Chouhdari, Arezoo; Shahrabi, Hadi; Pakdaman, Hossein; Heidari, Kamran; Gharagozli, Kourosh (Social Determinants of Health, 2019)
Background: Healthy lifestyle factors are associated with a lower risk of stroke. The current study aimed to describe lifestyle-related risk factors in ischemic stroke. Methods: In this cross-sectional study patients with ischemic stroke in two age groups assessed for lifestyle. Demographic characteristics (age, sex, BMI, marital status, educational level, job type as low or full stress, living area), lifestyle habits, and past medical history in two age groups collected in the structured form by researchers. Chi-square (Fisher’s exact) test for assessment of the statistical difference between categorical variables applied. Also, a multivariate logistic regression model was used to predict possible life-threatening lifestyles which can lead to stroke under the age of 50 (odds ratio, 95% confidence interval). All statistical tests were two-tailed and were performed with the use of PASW Statistics for Windows, Version 18.0. Chicago: SPSS Inc. P values <0.05 were regarded as significant. Results: Totally, 11.2% of ischemic stroke cases were 50≥ years old. In the multivariable logistic regression model higher BMI (P=0.02, OR =1.5, 95%CI=1.2 – 4.3), smoking (P<0.001, OR=1.8, 95%CI=1.08 – 2.56), alcohol drinking (P<0.001, OR=1.6, 95%CI=1.01 – 3.87), hookahs consumption (P<0.001, OR=1.2, 95%CI= 1.1 – 3.5) were predicting factors for ischemic stroke incidence in age ≤50 and only appropriate diet (low fat, sugar, salt, high fruits and vegetables) (P=0.01, OR= 0.7, 95% CI= 0.04-0.87) was preventive factors against stroke in age ≤50 years in compare with over 50. Conclusion: Based on this survey many lifestyle factors effects the incidence of ischemic stroke in any age group. Therefore, periodic monitoring and effective in educating healthy people should be planned.